(untitled) (Research in Agriculture Livestock and Fisheries, 2021)
The study focuses on comparing technical efficiency and profitability between Boro rice farmers and maize farmers in Dinajpur district consisting of 150 randomly collected samples which are analyzed with statistical software STATA 12.0 version. Stochastic Frontier Analysis (SFA) is used to accomplish the first objective where it is found that the maize farmers are efficient compared to boro-rice farmers. The deviation of the mean technical efficiency is estimated at 0.09. In addition maize farmers are also more profitable than boro-rice farmers estimated with a benefit Cost Ratio (BCR) of1.08 is for boro-rice and 1.26 is for maize production. The net profit for boro-rice is estimated as 10,527.60 Tk./ha whereas 28,966.40 Tk./ha for maize producers. However mean technical efficiency of boro-rice (0.44) and maize (0.53) cultivation clearly indicates that better utilization of resources will raise the efficiency and profitability for both crops production. Res. Agric., Livest. Fish.8(1): 51-56, April 2021